2016
DOI: 10.1021/acsami.5b11265
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and Resistance Switchings Induced by Electric Field in Epitaxial Mn:ZnO/BiFeO3 Multiferroic Heterostructures at Room Temperature

Abstract: Electric field induced reversible switchings of the magnetization and resistance were achieved at room temperature in epitaxial Mn:ZnO(110)/BiFeO3(001) heterostructures. The observed modulation of magnetic moment is ∼500% accompanying with a coercive field varying from 43 to 300 Oe and a resistive switching ratio up to ∼10(4)% with the applied voltages of ±4 V. The switching mechanisms in magnetization and resistance are attributed to the ferroelectric polarization reversal of the BiFeO3 layer under applied el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The observed ferroelectric polarization is not much enhanced with Pb doping when compared with BFO multiferroic systems that have been recently reported. 29,32,33 The small polarization here relates to the residual oxygen vacancies that may not neutralized by dopant ions. Another dopant, such as higher valence Ti ions (along B-site) for Fe 3+ , may stabilize the BFO structure with a low leakage of current.…”
Section: Resultsmentioning
confidence: 99%
“…The observed ferroelectric polarization is not much enhanced with Pb doping when compared with BFO multiferroic systems that have been recently reported. 29,32,33 The small polarization here relates to the residual oxygen vacancies that may not neutralized by dopant ions. Another dopant, such as higher valence Ti ions (along B-site) for Fe 3+ , may stabilize the BFO structure with a low leakage of current.…”
Section: Resultsmentioning
confidence: 99%
“…[77][78][79][80] Various organic compounds/GOhybrid materials have been createdbyusing physiochemical approaches, thereby improving the processability of these materials in different solvents and utilizing the outstanding properties of the attached molecules. [81] Aw ide range of organic compounds, including aromatic dyes, ionic liquids,a nd pyrene derivatives, have also been anchored onto GO nanosheets,either in ac ovalent or noncovalent manner, for applications in catalysis, electronic devices, and solar cells. Such GObased chemistry typically results in interesting properties and is promising for applications that require high chemical stability of the basal plane and tunable moieties at the multifunctional edge sites.…”
Section: Lbl Assembly:acase Study Of Graphene Oxidementioning
confidence: 99%
“…The unipolar, bipolar and nonpolar RS behaviors have been found in the epitaxial and polycrystalline thin lms even in the nano-islands and nanocapacitor arrays device structures of BFO, whose mechanisms have been mostly attributed to conductive lament, oxygen vacancy migration, charge trapping/detrapping process. 12,14,[22][23][24][25][26] However, very few works focused on the correlation and regulation behaviors between RS and magnetism switching in BFO. Recently, Sun et al, reported magnetic-eld controlled RS behaviors in Ag/ BiFeO 3 /g-Fe 2 O 3 /FTO device, in which the extra opposite direction electrical eld play a vital role in controlling the RS with the magnetic eld.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the main RS and magnetic variation mechanisms were mainly ascribed to the variation of oxygen vacancies regulated by ferroelectric polarization at the Mn:ZnO/BFO interface. 25 Chen et al reported the magnetization switching in the Au/BiFe 0.9 Mn 0.1 O 3 /Pt thin lm device modulated by unipolar RS process and reveal that such a magnetization switching is dominated by the conversion of Fe ion valence state between Fe 2+ and Fe 3+ , which is accompanied with the formation and the rupture of the conduction laments during the RS process. 13 However, our and related studies have demonstrated that the BFO/NSTO heterostructure exhibits bipolar RS effect and the ferroelectric polarization reversal on the interface play a dominant role on the RS behavior, which has a completely different mechanism from the conductive lament model.…”
Section: Introductionmentioning
confidence: 99%